A sub-wavelength scale acoustoelastic sonic crystal for harvesting energies at very low frequencies (<∼1 kHz) using controlled geometric configurations. (February 2017) - Ahmed, Riaz; Madisetti, Dylan; Banerjee, Sourav
Predictive design to control the geometric configurations of a novel sub-wavelength scale energy scavenger to harvest energy at lower sonic frequencies (<∼1 kHz) is presented. In this work, defying the conventional physics of structural resonance at lower frequencies, the traditional solution of large size harvesters is argued by adopting the physics of local resonance in designing the energy harvesters with sub-wavelength scale foot print. It is reported that during the local resonance, the wave energy passing through the acoustoelastic sonic crystals remains trapped within the soft matrix as the dynamic strain energy; hence, it is proposed to harvest that same trapped energy by strategically embedding the smart materials inside the matrix, capable of electromechanical transduction (e.g. lead zirconate titanate). The proposed acoustoelastic sonic crystal model was able to harvest energies at four different frequencies within <∼1 kHz with possible loading conditions and respective lead zirconate titanate placements. Through experimental validation, a particular acoustoelastic sonic crystal model with sub-wavelength geometry (∼3.65 cm) was investigated. Against 10 kΩ resistive load, a maximum power density of ∼92.4 µW/cm 2 was achieved. It is further reported that the geometrical model of the proposed harvesters can be predictively altered while filtering the acoustic waves and harvest the energy, simultaneously.